PENINGKATAN KEMAMPUAN DUTA GERMAS PENCEGAHAN COVID19 MELALUI PEERGROUPDI SMP SRIJAYA NEGARA PALEMBANG TAHUN2021 - Agustin, Ismar; Putri, Prahardian; Erman, Imelda (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Currently, the community is faced with a prolonged pandemic, namely the COVID-19 pandemic. Various steps have been initiated by the Indonesian government so that the spread of the virus can be controlled, including through GERMAS. GERMAS as a health program based on community empowerment in schools requires strengthening through the school GERMAS ambassador. Improving healthy life patterns/behaviors for junior high school students through increasing the ability of GERMAS ambassadors in preventing the spread of Covid-19. The solution to the problem is carried out by developing the ability of GERMAS ambassadors for junior high schools (SMP) in the application of GERMAS to prevent the spread of covid-19 through peer groups. The activity was carried out through the training stages of GERMAS ambassador, then GERMAS ambassador did socialization to peer groups through peer groups. The output produced is in the form of increasing the understanding and ability of the GERMAS ambassador and junior high school students in healthy living behavior through the GERMAS application to prevent the spread of Covid-19, in addition to producing the proposed IPR module and public service publications in the Sinta indexed Community Service Journal.